Review on in vitro antioxidant activities of curcuma species commonly used as herbal components in Indonesia - Rohman, Abdul; Widodo, Harto; Lukitaningsih, Endang; Mohamad, Rafi; Ahmad Fadzillah, Nurrulhidayah; Windarsih, Anjar (Rynnye Lyan Resources, 2020)
Free radicals, reactive nitrogen species (RNS) and reactive oxygen species (ROS) have been known to contribute several degenerative diseases such as cardiovascular diseases, aging, certain types of cancers, rheumatoid arthritis, neurodegenerative, and diabetes mellitus. In order to overcome the negative effects of these radicals, some scientists have explored some natural antioxidants from plants and it's by-products. The antioxidant can be defined as any substances or samples capable of inhibiting free radical reactions in the oxidation reaction. Due to curcuminoids contained, Curcuma species such as Curcuma longa, Curcuma heyneana, Curcuma mangga, and Curcuma xanthorriza were commonly used for herbal components in some traditional medicine. Several in vitro tests been introduced and used to measure antioxidant activities, namely radical scavenging assay using 2,2’-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+), ferric reducing antioxidant power (FRAP), ferric-thiocyanate, phosphomolybdenum method, cupric ion reducing antioxidant capacity, metal chelating power, beta-carotene bleaching linoleic-ferric-thiocyanate, and thiobarbituric acid methods. This review highlighted the antioxidant activities in vitro of C. longa, C. heyneana, C. mangga, and C. xanthorriza through several tests. To perform this review, several repute databases were analyzed and used. From this review, it can be stated that Curcuma species have powerful antioxidant activities, therefore they could be potential sources of natural antioxidants and can be used as food supplements. © 2019 The Authors. Published by Rynnye Lyan Resources.